A mechanistic model of cross-bridge migration in RBC aggregation and disaggregation - Maung Ye, Swe Soe; Kim, Sangho (Frontiers in Bioengineering and Biotechnology, 2022)
Red blood cells (RBCs) clump together under low flow conditions in a process called RBC aggregation, which can alter RBC perfusion in a microvascular network. As elevated RBC aggregation is commonly associated with cardiovascular and inflammatory diseases, a better understanding of aggregation is essential. Unlike RBC aggregation in polymer solutions (such as dextran in phosphate buffered saline) which can be well explained by polymer depletion theory, plasma-mediated RBC aggregation is more complex and involves both cooperative and competitive interactions between multiple molecules in the inter-surface attraction process. A favored approach in blood flow modeling that circumvents this complexity is to employ phenomenological models of aggregation that simply define the adhesion strength through the adhesion potential. However, since there is no mechanistic description of how the adhesion potential is dynamically changing, the existing adhesive potential models may fail to describe some peculiar aggregation scenarios in plasma. Previous studies have demonstrated the dominant role of fibrinogen (Fg) in promoting aggregate formation and recent cell-force spectroscopy (CFS) experiments on interacting RBC doublets in plasma have reported an inverse relationship between disaggregation force and the adhesive contact area between RBCs. This has led investigators to revisit the hypothesis of inter-RBC cross-bridging which involve cross-bridge migration under interfacial tension during the forced dissociation of RBC aggregates. In this study, we developed a theoretical model of the Fg-dominant RBC aggregation mechanism in plasma that mechanistically represents the migrating cross-bridge hypothesis. We examined the parameters and assumptions for the aggregation model to best match optical tweezers experimental data in the literature. Our cross-bridge-migration model (CBMM) considers the convection-diffusion dynamics of the mobile cross-bridging Fg-complexes (mFg) on the RBC surface, spatially-limiting effects of cross-bridge length and site availability between adjacent RBCs and the role of intercellular friction in modulating RBC aggregation dynamics.